Dampak Wabah Virus Corona (Covid-19) Terhadap Kegiatan Ekonomi Usaha Peternakan Ayam Broiler Kemitraan di Kabupaten Banyumas - Suryani, Jihanita Arfan; Sugiarto, Mochamad; Wakhidati, Yusmi Nur (ANGON: Journal of Animal Science and Technology, 2020)
Background. Research on the Impact of Corona Virus Outbreak (Covid-19) on the Economic Activities of Partnership Broiler Chicken Farming in Banyumas Regency was conducted on April 30th, 2020 until May 14th, 2020 in Banyumas Regency. The corona virus outbreak not only caused a general economic impact but also affected the economic activities of the partnership broiler chicken farming business, especially in Banyumas Regency. This study aims to determine the profile of partnership broiler breeders in the Banyumas Regency and to know the economic activities of partnership broiler chicken farms in Banyumas Regency before and during the corona virus outbreak which includes the ease of selling broiler chickens, selling prices, and getting business profits. Materials and methods. This research was conducted by the survey method with the technique of determining samples using accidental sampling, with criteria to have conducted a broiler chicken farming partnership for a minimum of one year. The number of respondents is at least 30 farmers. Questionnaires were given online using google forms. The analysis used is descriptive with the measurement mode or value that appears most often. Results. The results of the research showed that the partnership broiler breeders in Banyumas Regency have been raising chicken for over 10 years on average, but with a relatively small population scale of 1,000-5,000 with most farmers having high school education and making livestock business as the major occupation. Before the corona virus outbreak, farmers found it easy to sell their products, got good selling prices, and felt easy to get business profits, while during the corona virus outbreak, farmers found it difficult to sell their products, got a lower selling price, and felt difficult to get business profits. Conclusion. The economic activities of the partnership broiler chicken farming business during the corona virus outbreak have a direct impact on farmers, namely in the ease of selling and of obtaining business profits.